Depresi Pada Mahasiswa Keperawatan - Warnidar, Eka; Riani, Eka Oktarina; Elvin, Said Devi; Afdhal, Afdhal; Ritawati, Ritawati; Nurhayati, Nurhayati (Journal Keperawatan, 2024)
Background: Depression is a very important component in the implementation of education and student development, because it can increase productivity and success in the academic and training activities they undergo. To determine the appropriate intervention to reduce student depression, empirical evidence is needed about the level of depression at each level of students in the Diploma III Nursing Program. Purpose: To identify differences in depression in Diploma III students suffering from each level. Methods: This research has an analytical survey design using a comparative approach. The number of samples in this study was 642 respondents. The questionnaire used was the Center for Epidemiologic Studies Depression Scale. Results: The results of this study show that there is a significant difference in average depression between levels in Diploma III Nursing Polytechnic Health students with the results of the Kruskall Wallis test p-value: 0.02 (p<0.05). Conclusion: There are differences in levels of depression in level I, II and III nursing students.